A Simulation Study of Downdraft Gasification of Oil-Palm Fronds Using ASPEN PLUS - Atnaw, Samson Mekbib; Sulaiman, S. A.; Yusup, Suzana (2010)
The use of biomass gasification for conversion of hydrocarbons to permanent fuel gas mainly composed of carbon monoxide and hydrogen, dates back to late 1700. However, the successful design and operation of gasifiers is not an easy task. No clear cut methods of performance prediction of gasifiers is yet available as the thermodynamics of gasifier operation is less understood and highly dependent on the specific biomass feedstock used. In this paper the performance study of downdraft gasification of oil-palm fronds, is carried out making use of ASPEN PLUS process simulator software, to study the effect of operating conditions (zone temperature, operating pressure, air fuel ratio and moisture content) on syngas composition. In the current paper the pyrolysis yield is calculated from the ultimate analysis (CHNS test) values of the oil-palm fronds, rather than approximating typical yield distribution for pyrolysis products. The results of the simulation showed better agreement with the syngas composition results of other authors. From the simulation study it is shown that higher mass fraction of CO and CH4 can be obtained at lower Air-Fuel ratio, and lower pressure (below 5 bars). The mass fraction of CO increases sharply with increase in the oxidation zone temperature, for the temperature range of 500-700°C.